2015
DOI: 10.1159/000369687
|View full text |Cite
|
Sign up to set email alerts
|

AMP-Activated Protein Kinase Alleviates Extracellular Matrix Accumulation in High Glucose-Induced Renal Fibroblasts through mTOR Signaling Pathway

Abstract: Background/Aims: Extracellular matrix accumulation contributes significantly to the pathogenesis of diabetic nephropathy. Although AMP-activated protein kinase (AMPK) has been found to inhibit extracellular matrix synthesis by experiments in vivo and vitro, its role in alleviating the deposition of extracellular matrix in renal interstitial fibroblasts has not been well defined. Methods: Currently, we conducted this study to investigate the effects of AMPK on high glucose-induced extracellular matrix synthesis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 40 publications
1
18
0
Order By: Relevance
“…Hyperglycemia leads to nephropathy by various mechanisms, such as increased endothelial cell permeability to albumin, hypertrophy, thickening of the basement membrane and renal fibrosis [27, 28]. In the present study, our data demonstrated that the expressions of GSK-3β, β-catenin, α-SMA, and MMP9 were increased under high glucose condition, and these changes were attenuated by paricalcitol pretreatment.…”
Section: Discussionsupporting
confidence: 65%
“…Hyperglycemia leads to nephropathy by various mechanisms, such as increased endothelial cell permeability to albumin, hypertrophy, thickening of the basement membrane and renal fibrosis [27, 28]. In the present study, our data demonstrated that the expressions of GSK-3β, β-catenin, α-SMA, and MMP9 were increased under high glucose condition, and these changes were attenuated by paricalcitol pretreatment.…”
Section: Discussionsupporting
confidence: 65%
“…AMPK, a serine/threonine kinase, has been considered as a metabolic switch to maintain energy homeostasis (Bolster et al, ; Luo et al, ). Meanwhile, AMPK promotes autophagy by indirect inhibiting mTOR under serum deprivation stresses (Shaw, ).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hypoxia often occurs in the kidney tissues of many patients with CKD (18). Tubulointerstitial fibrosis leads to thickness of the tubular basement membrane and accumulation of interstitial ECM (34)(35)(36)(37). In this study, hypoxia upregulated the expression of genes related to the basement membrane.…”
Section: Discussionmentioning
confidence: 99%